الأبعاد الفلسفية للحداثه عند محمد أركون - لوشه راضية; العروم ناريمان (جامعة الوادي - University of Eloued, 2025)
يُعد محمد أركون من أبرز المفكرين المعاصرين الذين سعوا إلى تجديد الفكر الإسلامي، من خلال تبنّي مفاهيم الحداثة وأدواتها النقدية. حيث اعتبر الحداثة رؤية عميقة، يتجاوز بذلك مرحلة من مراحل التاريخية، إلى ممارسة التفكير النقدي وتفكيك الفكر الديني الجامد. وقد سعى إلى دمج الفكر الإسلامي مع الأبعاد الفلسفية التي تتداخل فيها الدين، والعلم، والتاريخ، واللغة. حيث ركز أركون على إمعان العقل النقدي، بدلًا من التسليم بالنصوص الدينية تسليمًا قطعيًا، وإعادة فهم التراث الإنساني وقراءته قراءة جديدة، بأدوات إبستمولوجية وأنثروبولوجية، للتواصل مع الواقع المعاصر، وبناء المستقبل، وتحرير العقل الديني ليكون قادرًا على التفاعل مع العالم المتغير. كما اعتبر أن الحداثة هي قراءة جديدة للتراث الإسلامي، وإعادة فهمه وتأويله، ليكون أساس بناء حداثة إسلامية أصيلة، لا تنفصل عن الجذور، لكنها متطلعة للمستقبل. وبهذا، ليست الحداثة عند أركون تقليدًا للغرب، بل هي ممارسة عقلية نقدية تقوم على مساءلة المسلّمات، وبلورتها وفق الأطر الإسلامية، وإعادة بناء الفكر على أسس عقلانية وعلمانية، من أجل ممارسة الحداثة الفكرية، بهدف بناء فكر إسلامي حديث. Abstract: Mohammed Arkoun is one of the most prominent contemporary thinkers who sought to renew Islamic thought by adopting the concepts and critical tools of modernity. He viewed modernity as a profound vision that transcended a historical stage, to practice critical thinking and deconstruct rigid religious thought. He sought to integrate Islamic thought with the philosophical dimensions that intertwine religion, science, and history. In language, Arkoun established a critical mind instead of accepting religious texts as absolute, and aimed to re-understand human heritage and read it with new epistemological and anthropological tools. This approach was meant to communicate with contemporary reality, build the future, and liberate the religious mind to be able to interact with the changing world. He also considered that modernity is a new reading of the Islamic heritage — a re-understanding and interpretation of it — to be the basis for building an authentic Islamic modernity that is not separate from its roots, but rather looks to the future. Thus, for Arkoun, modernity is not an imitation of the West, but rather a critical mental practice based on questioning established principles and reshaping them according to Islamic frameworks. It involves rebuilding thought on rational and secular foundations in order to practice intellectual modernity, with the aim of building a modern Islamic thought.
مذكرة ماستر قسم الفلسفة تخصص فلسفة عامة.
Keywords: فلسفة الحداثة; محمد أركون; العقل الاسلامي; العلمانية; The Philosophy of Modernity; Mohammed Arkoun; The Islamic Mind; Secularism